Los sistemas de producción y comercialización de los productos originarios de la zona en la parroquia muyuna, cantón Tena, provincia de napo y su efecto en la economía familiar, periodo 2016. - Quinapallo Aguinda, Karina Del Rocio (2017)
area in the parish of Muyuna, Tena, Province of Napo and this effect in the family economy, Period 2016.”, which seeks to provide the necessary information on the production and marketing of the parish of Muyuna, for the decision-making and can contribute to improve the production and the viability of the products that farmers cultivate in order to obtain economic income for their families. Chapter I: Referential Framework, is composed of: problem statement, justification of research; and also the general and specific objectives. Chapter II: State of Art, is composed of background and theoretical foundation; within which definitions are developed, the importance of production and marketing. Chapter III: Methodology, which outlines the research method, as well as information on the production and marketing of each of the agricultural products that are grown in the area. Chapter IV: Results and Discussion, establishment of information that was obtained through research through the survey. Chapter V: Conclusions and Recommendations, these are established once the present investigation has been completed.